Analysis of TP53 aflatoxin signature mutation in hepatocellular carcinomas from Guatemala: A cross‐sectional study (2016‐2017). Issue 2 (6th May 2020) - Alvarez, Christian S.; Ortiz, Jeremy; Bendfeldt‐Avila, Giovanna; Xie, Yi; Wang, Mingyi; Wu, Dongjing; Higson, Herbert; Lee, Elisa; Teshome, Kedest; Barnoya, Joaquin; Kleiner, David E.; Groopman, John D.; et al.
Abstract: Background and aims: Guatemala has the highest incidence of hepatocellular carcinoma (HCC) in the Western hemisphere. The major risk factors in Guatemala are not well characterized, but the prevalence of hepatitis B virus (HBV) and hepatitis C virus (HCV) appears to be low, while the prevalence of aflatoxin (AFB1 ) exposure appears to be high. To examine whether AFB1 may contribute to the elevated incidence of HCC in Guatemala, this study examined the frequency of the AFB1 ‐signature mutation in the TP53 gene (R249S) as well as other somatic mutations. In addition, we assessed whether the frequency of the TP53 mutation differed by sex. Methods: Formalin‐fixed, paraffin‐embedded (FFPE) HCC tissues were obtained from three hospitals in Guatemala City between 2016 and 2017. In addition, tumor tissues preserved in RNAlater were also obtained. Sociodemographic and clinical information including HBV and HCV status were collected. Targeted sequencing of TP53 was performed in the FFPE samples, and a panel of 253 cancer‐related genes was sequenced in the RNAlater samples. Results: Ninety‐one FFPE tissues were examined, from 52 men and 39 women. Median (IQR) age at diagnosis was 62 (51‐70). Among those with known HBV and HCV status, two were HBV+ and three were HCV+. Overall, 47% of the HCCs had a TP53 mutation. The AFB1 ‐signature R249S mutation was present in 24%. No overlap between the R249S mutation and HBV+ was observed in this cohort. Among 18 RNAlater samples examined, 44% had any TP53 mutation and 33% had the R249S mutation. Other somatic mutations were identified in known HCC driver genes. Conclusions: The presence of the TP53 R249S mutation in the samples studied suggests that AFB1 may contribute to the high incidence of HCC in Guatemala. The proportion of HBV+ tumors was low, suggesting that AFB1 may be associated with HCC in the absence of concomitant HBV infection. Further investigation of AFB1 and other risk factors for HCC in Guatemala is warranted.